(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2015)
Central pontine myelinolysis (CPM) is a complication of treatment of patients with severe hyponatremia. The microscopic appearance of central pontine myelinolysis is loss of myelin with sparing of axons, without evidence of inflammation. The abnormalities associated with central pontine myelinolysis are readily identified on magnetic resonance imaging scans. A patient with central pontine myelinolysis following rapid correction of hyponatremia was studied with magnetic resonance imaging soon after onset of tetraplegia & dysarthria. Affected central pontine white matter showed restricted diffusion on diffusion-weighted images associated with hyper signal on T2-W & FLAIR images. MRI with dedicated sequences is the modality of choice for early detection of osmotic changes in the brain. DOI: http://dx.doi.org/10.3329/cmoshmcj.v13i1.19427